Autoimmune intestinal leiomyositis as a rare cause of chronic intestinal pseudo-obstruction in children: Case report with literature review - Milovanović Ivan D.; Popovac Nevena; Sretenović Aleksandar; Ristić Nina; Janković Radmila (Srpski Arhiv za Celokupno Lekarstvo)
Introduction. Chronic intestinal pseudo-obstruction represents a group of rare disorders characterized by impaired gastrointestinal motility in the absence of mechanical bowel obstruction. These disorders can be primary or secondary, with autoimmune intestinal leiomyositis falling into the latter category. This condition is observed in adolescence and adulthood but is very rarely seen in children, especially in infancy. Case outline. A nine-month-old male infant was hospitalized due to persistent vomiting, abdominal bloating, and distension. After diagnostic evaluations and failure of conservative treatment measures, surgical formation of an ileostomy was performed. During the procedure, intestinal samples were obtained, revealing T lymphocyte infiltration of the intestine. Immunological blood analyses showed elevated serum immunoglobulins and smooth muscle autoantibodies. Combined with histological findings and elevated inflammatory markers, a diagnosis of autoimmune intestinal leiomyositis was established. Immunosuppressive therapy was initiated, leading to normalization of inflammatory markers and resolution of clinical symptoms. After four years of immunomodulatory therapy, the ileostomy was closed, and intestinal biopsies showed no inflammatory infiltrates. Five years later, the boy remains free of gastrointestinal symptoms, with normal growth and development. Conclusion. Although a rare condition, autoimmune intestinal leiomyositis is an important differential diagnostic entity in chronic intestinal pseudo-obstruction. Early disease recognition with intestinal biopsies, coupled with prompt and aggressive immunosuppressive therapy, enables favorable therapeutic outcomes.